PULMONARY FUNCTION TESTS IN PROFESSIONAL WELDERS - DR CHANDRASHEKHAR D DANGE,; SMT ANITA J JADHAV, (International Journal of Pharma and Bio Sciences, 2016)
The respiratory effects of exposure to welding fumes have been investigated in numerous studies; but the results of these studies have not been consistent. The aim of the present study was to investigate the respiratory effects of welding fumes exposure in a group of manual arc welders exposed primarily to welding processes in confined spaces without respiratory protection. The 25 welders were subjected to spirometry to assess the respiratory functions. Forced expiratory volume at the end of one second i.e. FEV1 and forced vital capacity i.e. FVC were considered. In the present study, the FEV1/FVC ratio less than 0.7 the subjects were 7 and more than 0.7 were 18. This indicates that 7 subjects tend to have obstructive respiratory pathologies and 18 were having either pathologies normal or restrictive respiratory. Welding fumes may impair respiratory function and cause bronchitis. It is concluded that welders are at risk of respiratory dysfunction and should take protective measures such as avoid smoking and use masks.